2003
DOI: 10.1002/pen.10031
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical relaxations in heat‐aged polycarbonate. Part I: Comparison between two molecular weights

Abstract: As part of a wider research program related to polycarbonate embrittlement, the effects of heat-aging on mechanical relaxation behavior have been studied by examining the relationship between secondary transitions and stress relaxation behavior. In this Part I, the differences in response between two molecular weight polycarbonates (PC) are compared for injection molded samples. Dynamic mechanical spectra showed that the presence of an intermediate p transition (-80°C) is strongly dependent on molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The existence of the β 1 mode for the quenched samples should be evidenced in the future by complementary studies at lower frequencies, for example, or by a dielectric study. Lee‐Sullivan has already observed β 1 and β modes at the same time during a DMA study of PC; this tends to prove that the β 1 mode exists independently of the thermal treatment 32. The existence of this relaxation mode at about 35°C should be at the origin of the behavior of PC samples after a second quenching; the difference between the first and the second quenching is probably linked to the relaxation time of the molecular segments which are moving at 40°C.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The existence of the β 1 mode for the quenched samples should be evidenced in the future by complementary studies at lower frequencies, for example, or by a dielectric study. Lee‐Sullivan has already observed β 1 and β modes at the same time during a DMA study of PC; this tends to prove that the β 1 mode exists independently of the thermal treatment 32. The existence of this relaxation mode at about 35°C should be at the origin of the behavior of PC samples after a second quenching; the difference between the first and the second quenching is probably linked to the relaxation time of the molecular segments which are moving at 40°C.…”
Section: Resultsmentioning
confidence: 75%
“…Lee‐Sullivan et al as well as other authors have observed this peak and they have concluded that it was insensitive to thermal history, elusive and unaffected by thermal ageing 32, 38, 39. The origin of this relaxation mode remains unclear; it is simply described to be due to segmental motions of intermediate length, i.e., between long chain motions occurring at the α glass transition and short chain motions responsible for the γ relaxation 32…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…A strength of our technique is that it is very sensitive to the low phase angles that are typical of glassy polymers. As a result, physical and chemical aging processes, such as shifts in the β relaxation 40 that affect the fracture behavior of glassy polymers, 41 can be readily investigated. The phase angles for each cross-linker ratio (sample 1 from Table 1 in each case) are plotted as a function of curing time in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…As for the case of neat PC, this behavior could be linked to the existence of a molecular relaxation located around 358C. 11 We will recall here that DMA experiments presented in part I have demonstrated the existence of this relaxation in neat PC specimens submitted to annealing treatments.…”
Section: Effect Of Second Quenching Temperaturementioning
confidence: 96%